2020
DOI: 10.1515/openms-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Domestic and Transboundary Conflicts on Militarization

Abstract: Security issues are the global concern nowadays, which triggers government spending on military equipment and supply chain. This paper analyzes the global perspective of cohesion indicators on Militarization by using 177 countries panel data from the Years 2011-2018 based on middle/lower and high-income groups. By applied OLS and Fixed Effect modelling, we explored the idea that Group Grievance and Population Growth Rate have a significant impact on Militarization in both income groups worldwide. However, midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, mere corruption is not responsible for institutions' deterioration [ 70 ] because other State-fragile factors such as demographic, legal, and business regulation also significantly affect institutional quality. These volatile indicators should consider taking corrective action in social, economic, security, and political context [ 44 ] for the well-being of the public [ 45 ] in developing and under-developed countries [ 7 , 8 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mere corruption is not responsible for institutions' deterioration [ 70 ] because other State-fragile factors such as demographic, legal, and business regulation also significantly affect institutional quality. These volatile indicators should consider taking corrective action in social, economic, security, and political context [ 44 ] for the well-being of the public [ 45 ] in developing and under-developed countries [ 7 , 8 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some Fragile state indicators do not show clear pictures in combination, which need to be studied separately as External Intervention shows a significant impact on institutions' quality, which has already been evidenced by the studies [ 19 , 46 , 47 ]. In panel data study observed that the fragility index value has less robust results than an individual indicator as used in this study [ 44 , 45 , 71 ]. Voice & accountability also have significantly impacted institutional quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also examined that it can create a conflict of interest among policymakers that intimate the shredding of political powers (Martin & Vanberg, 2020 ). Moreover, this friction or conflicts of interest in bipartisan political ideologies leads to inefficiency in policymaking (Abbas, Gillani, et al, 2020 ; Abbas, Xu, et al, 2020 ; Chan & Fan, 2020 ).…”
Section: Research Backgroundmentioning
confidence: 99%